Self-Efficacy and External Locus of Control as Predictors of Participant Roles in Relational Aggression - Levy, Michal (Journal of interpersonal violence, 2022)
We examined the extent to which the perceived behavioral control factors of pro-social, emotional, or verbal-social self-efficacy (SE) as well as external locus of control (LOC) explain the variance between different participant roles: relational aggressors, relational victims, relational aggressive-victims, and bystanders. Participants included 1,518 adolescents (61.6% boys and 38.4% girls) from 15 Israeli middle and high schools. Multinomial logistic regression models indicated relational aggressors, and aggressive-victims had lower pro-social SE and higher verbal-social SE than relational victims and bystanders. Relational aggressors, aggressive-victims, and victims had more extensive external LOC than bystanders. The theoretical contribution of verbal-social SE is discussed, and practical implications are highlighted, in particular, regarding the relational aggressive-victim, who exhibits high-risk behaviors.